Factors affecting implementation of mindfulness in hospital settings: A qualitative meta-synthesis of healthcare professionals' experiences - Randi Karkov Knudsen; Sine Skovbjerg; Elna Leth Pedersen; Camilla Littau Nielsen; Marie Højriis Storkholm; Connie Timmermann (Elsevier, 2024)
Background: Researchers have found that mindfulness-based interventions can reduce stress and improve mental health in healthcare professionals, as well as support relationship building, communication, and compassionate care. However, few researchers have systematically examined what determines successful implementation in hospital settings, which is essential for integrating research in clinical practice. Objectives: The aim of this study was to synthesize qualitative data regarding healthcare professionals' experiences of factors affecting implementation of mindfulness in hospital settings and outline recommendations for clinical practice. Design: A systematic review and meta-synthesis of qualitative studies. Data sources: A systematic search was conducted in six databases; Scopus, PubMed, CINAHL, PsycINFO (Ovid), Web of Science, and ProQuest Dissertations and Theses Global. The inclusion criteria were: 1) Healthcare professionals engaged in patient care in hospital settings, 2) Mindfulness-based interventions defined by Crane and colleagues', and 3) Primary studies using a qualitative design. Review methods: Multiple researchers were engaged in screening, quality assessment, data extraction, and interpretation of the results. Thematic synthesis described by Thomas and Harden guided the data analysis. Reporting followed Enhancing Transparency in Reporting the Synthesis of Qualitative Research (ENTREQ). Results: Eighteen studies were included. We identified three overall themes of importance for successful implementation: 1) Buying In, 2) Allocating time and space, and 3) Keeping it going. The results revealed that cultural values, held beliefs about mindfulness, inter-professional relationships, and context-related factors such as time and space could affect implementation of mindfulness in hospital settings. Conclusion: Based on the results, we formulated eight recommendations to guide stakeholders and hospital management in planning implementation of mindfulness in hospital settings. However, to confirm the results, more research where mindfulness implementation is the primary aim is needed.